Improved figures of merit of nano-Schottky diode by embedding and characterizing individual gold nanoparticles on n-Si substrates. (8th January 2020) - Abbas, Yawar; Rezk, Ayman; Anwer, Shoaib; Saadat, Irfan; Nayfeh, Ammar; Rezeq, Moh'd
Abstract: Improving Schottky diode characteristics in semiconducting devices is essential for better functionality in electronic and optoelectronic devices at nanoscale. In this paper, we investigate the electric transport characteristics of a gold (Au)-tip/n-Si-based nano-Schottky diode by using a conductive-mode atomic force microscope (CAFM). First, 10 nm average diameter Au nanoparticles (NPs) are monodispersed on the highly cleaned n-type Si substrate using an optimized spin-coating technique. The controlled and well dispersed NPs are confirmed by using the AC imaging mode of the AFM. The electrical characteristics are established by using an Au-coated AFM tip, by either soft engaging at the surface of the n-Si substrate or at the top of an individual Au NP. Landing of the AFM tip on the NP or n-Si substrate is validated by the force curves of the AFM. From the localized CAFM electrical characteristics, we observed the improvement in the figures of merit (FOM) that characterize the rectification performance including the (1-V) asymmetry ( f ASYM ), and the turn-on voltage due to placing the Au NP between the AFM tip and n-Si substrate. These improved FOM of the nanoscale diodes are explained based on the increase in the tunneling current at the nanoscale Au-NP/n-Si interface. Moreover, the nanoscale control of interface structure is extremely important to improve the characteristics of nano-Schottky diodes.